Service science and logistics informatics : innovative perspectives - Luo, Zongwei, 1971- (Hershey, PA : Information Science Reference, 2010)
'This book provides both business and IT professionals a reference for practices and guidelines to service innovation in logistics and supply chain management'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business logistics -- Information technology; Service industries -- Information technology